EXPLORING PERSONIFICATION AND PLAYFULNESS IN ROGER MCGOUGH’S “PILLOW TALK” WITH OCCASIONAL AI ASSISTANCE - Boltaboyeva Onaxon Xushnud qizi (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This article analyzes Roger McGough’s poem “Pillow Talk”, focusing on its use of personification, humor, and rhythm to portray childhood imagination. AI was occasionally used to assist in interpreting complex poetic features.